PEMBANGUNAN SISTEM INFORMASI ALUMNI BERBASIS WEB PADA PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS DIPONEGORO - Yusi Ardi Binarso; Eko Adi Sarwoko; Nurdin Bahtiar (Journal of Informatics and Technology, 2012)
Informatics Engineering Major of Diponegoro University in Faculty of Sains and Math is a course that have graduated many students who have competency at information technology. However, the communicator unavailability between alumnus, make other alumnus information obtaining or information sharing, such as job vacancies, difficult. With the utilization of internet technology, a Web-Based Alumnus Information System can be used as a communicator between the alumnus and make information distribution become quickly and easily. The Web-Based Alumnus Information System at Informatics Engineering Major of Diponegoro University was built using Waterfall model, PHP as programming language, and MySQL as database management system. The Web-Based Alumnus Information System can help the Informatics Engineering Program on alumnus data management, report making, and facilitate the alumnus to obtain information about other alumnus, news about campus, job vacancies, and scholarship.